From mythical ‘standard’ to standard reality: The need for alternatives to standardized English language tests - Jenkins, Jennifer; Leung, Constant (Language teaching, 2019)
This position paper builds on three of our earlier publications on the same subject (Jenkins & Leung 2014; Leung, Lewkowicz & Jenkins 2016; Jenkins & Leung 2017), as well as a number of conference papers we have given both jointly and individually. However, what we have not done up to this point is to propose alternatives to the large-scale standardized English tests administered by the major international examination boards, of which we have been so critical, despite the fact that we have been discussing other possibilities among ourselves for several years. The opportunity to publish a position paper on English language assessment therefore provided an ideal opportunity to present our alternatives, and this we do in the final part of the paper.